Commodity and financial market trends and the growth of bank assets: the case of equity-based banking - Haque, Ahasanul; Jahan, Irfath; Chowdhury, Naila Anwar; Rahman, Mahbubur (Research Publishing Academy (RPA), 2019)
The current paper has empirically examined the role of commodity and financial market attributes in assessing the performance of the banking sector by using total assets of equity-based banks as the primary performance indicator. The commodity market is represented by the trends present in the prices of gold, oil and wheat, while the financial market is represented by the world stock index. The findings suggest that oil and gold prices have a positive impact on total bank assets, whereas wheat price and world stock index have negative effects. The study contributes to the literature of commodity and financial market trends identifying the factors that are responsible for enhancing the financial performance of the banking sector based on economic theories. Regression analysis has been used for testing the proposed hypotheses. It is hoped that an examination of the relationship between commodity, financial market attributes and performance of the banking sector will provide meaningful insights regarding the implementation of theoretical knowledge for enhancing banking performance. The study provides a comprehensive concept for understanding the overall wheel of relationships responsible for improving the world economy.